2020
DOI: 10.1016/j.ijrobp.2019.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Oligometastatic Patients After Conventional or Stereotactic Radiation Therapy to Bone Metastases: An Analysis of the PRESENT Cohort

Abstract: This study shows the paradigm shift toward radical treatment in oligometastastic disease. Survival outcomes of patients with oligometastates are improving, and therefore optimization of palliative care is needed. Clinical local control rates are higher after stereotactic body radiation therapy to bone metastastes compared with conventional radiation therapy, but stereotactic body radiation therapy does not improve pain response or quality of life in oligometastastic patients. Purpose: Stereotactic body radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…It has been hypothesized that the duration of response is longer after SBRT because of higher local control. 9,30 Because only 39% of the patients completed the questionnaires at all follow-up time points, we were unable to make a reliable estimate of the duration of pain response to confirm this suggestion. Furthermore, local control was not assessed in the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been hypothesized that the duration of response is longer after SBRT because of higher local control. 9,30 Because only 39% of the patients completed the questionnaires at all follow-up time points, we were unable to make a reliable estimate of the duration of pain response to confirm this suggestion. Furthermore, local control was not assessed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Palliative radiation therapy (RT) is a proven effective and widely accepted treatment modality for metastatic bone pain. 3,4 Pain response after conventional RT (cRT) is similar in patients treated with single-fraction (8 Gy in 1 fraction) and multifraction (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Gy in 5-10 fractions) RT. 1,5,6 It has been suggested that dose escalation, and more specifically dose escalation per fraction, could improve pain response in patients with metastatic bone pain.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is not a comparative trial, EBRT, the current gold standard for pain palliation from osseous metastases, is limited in effectiveness with partial and complete response estimated at 60 and 33%, respectively [ 20 ]. Attempts to improve on palliation using SBRT failed to produce any meaningful differences in two prospective comparative trials [ 21 , 22 ]. A recently published randomized controlled trial did demonstrate differences, but these were not evident until 3 months post-treatment and the SBRT arm suffered from radiation-induced fractures as well as pain flare at 1-month in 11 and 43% of subjects, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Dutch Bone Metastasis Study, however, no difference in pain response was seen in patients surviving more than one year after a single fraction of 8 Gy or fractionated conventional radiotherapy [60]. An analysis of the prospective PRESENT cohort including those patients with oligometastatic bone disease showed higher clinical local control rates after SBRT compared to conventional radiotherapy, but SBRT did not improve pain response, duration of response or quality of life [89]. No difference in pain response was seen after stratification by radiation dose (8 Gy in one fraction vs 30 Gy in 10 fraction vs SBRT).…”
Section: Recommendationmentioning
confidence: 96%